Deflection of mesoscopic atomic superpositions via superradiance and superabsorption - Rocha, Leandro Manoel Rocha da (2024)
In this work we will deal with the effects of a coherent electromagnetic field acting on an atomic dipole gas confined to a cavity. It is known from (5) that in such conditions, if we a have moderately dense sample of N 2-level atoms, we can observe the presence of superradiance, i.e., the enhanced emission of a coherent pulse of intensity proportional to N2 and, in a smaller scale, the enhanced absorption as well (14). When coupling this sample to a quantum electromagnetic field via Tavis-Cummings interaction we are able to enhance even more the superabsorption as well as the superemission to a lesser degree in such a way as to almost equate the intensities of both processes and give rise to interleaved oscillations between them in both field and sample resulting in the phenomenon of many-body Rabi oscillations described in (1). However, it is to expect that, due to momentum conservation, such a phenomenon would cause a deflection on the atoms of the sample in a small time interval, after which we would have a mesoscopic superposition containing all the information related to the prior state. Our main goal is the study of the deflection suffered by the atoms of such a sample and how it relates to the state before the emission. We solve the time-dependent non-linear Hamiltonian related to the superradiant emission/superabsorption via the Lewis-Riesenfeld invariant method. At the end we will show how the macroscopic states were prepared to obtain our results.